Validation of bedside ultrasound to predict lumbar muscle area in the computed tomography in 200 non-critically ill patients: The USVALID prospective study. Issue 4 (April 2022) - Fischer, Arabella; Hertwig, Anatol; Hahn, Ricarda; Anwar, Martin; Siebenrock, Timo; Pesta, Maximilian; Liebau, Konstantin; Timmermann, Isabel; Brugger, Jonas; Posch, Martin; Ringl, Helmut; Tamandl, Dietmar; et al.
Summary: Background & aims: Skeletal muscle area (SMA) in the computed tomography (CT) at the third lumbar vertebra (L3) level is a proxy for whole-body muscle mass but is only performed for clinical reasons. Ultrasound is a promising tool to determine muscle mass at the bedside. It is still unclear how well ultrasound and which ultrasound measuring points can predict CT L3 SMA. Methods: This prospective observational trial included 200 non-critically ill patients, who underwent an abdominal CT scan for any clinical reason within 48 h before the ultrasound examination. Ultrasound muscle thickness was evaluated at 3 measuring points on the thigh and 2 measuring points on the upper arm with minimal compression. On the CT scan, the entire L3 SMA was measured based on Hounsfield units. Using a model selection algorithm based on the Bayesian information criterion (BIC) and clinical considerations, a linear prediction model for CT L3 SMA based on the ultrasound muscle thickness and other independent variables was fitted and assessed with cross-validation. Results: 67, 5% and 32, 5% of the patients were from surgical and medical wards, respectively. Mean ultrasound muscle thickness values were between 2, 2 and 3, 6 cm on the thigh and between 1, 4 and 2, 8 cm on the upper arm. All ultrasound muscle thickness values were higher in men than in women (P < 0, 05). CT L3 SMA was 40 cm 2 higher in men than in women (P < 0, 001). The final prediction model for CT L3 SMA included the following 4 independent variables: ultrasound muscle thickness at the ventral measuring point of the thigh in the short-axis plane, sex, weight, and height. It had a similar BIC (BIC of 1515) compared to larger models with 6–8 independent variables including multiple ultrasound measuring points (BIC of 1506–1519). Additional clinical considerations to choose the final model were less time consumption when measuring a single ultrasound measuring point and better anatomical overview at the short-axis plane. The final model predicted CT L3 SMA with a R 2 of 0, 74 (P < 0, 001) and a cross-validated R 2 of 0, 65. Conclusions: One single ultrasound measuring point at the thigh together with sex, height and weight very well predicts CT L3 SMA across different clinical populations. Ultrasound is a safe and bedside method to measure muscle thickness longitudinally to monitor the effects of nutrition and physical therapy.